Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Green extraction of non-starch polysaccharides from millet using a deep eutectic solvent: structural elucidation and structure-activity relationship of their inhibition of α-glucosidase - Yuxin Li; Rui Fang; Xia Tang; Pravin Ojha; Jingke Liu; Qinghai Sheng; Liangfu Zhou (Food Chemistry, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Comprehensive time-frequency analysis of multistage and multiscale propeller cavitation-induced pressure impacts on the ship hull - Guoshou Zhao; Heng Liu; Rui Wu; Sheng Ji (Ocean Engineering, 2026)

Effect of first-stage anode axial position on discharge characteristics of a double-stage anode layer thruster - Rui Ding; Sheng Wen; Zhihao Liu; Jia Liu; Guanrong Hang; Yan Zhang; Ximing Zhu; Yongjie Ding (Advances in Space Research, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Tectonically driven erosion with climatic modulation across the southern Tibetan Plateau: Insights from 10Be erosion rates - Jia-Qi Sun; Jin-Gen Dai; Xu Han; Matthew Fox; Guang-Sheng Ren; Zhi-Cheng Yu; Bo-Rong Liu; Xiang-Rui Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Study on the synergistic effect of coal-oil co-liquefaction and analysis of liquefied oil products - Jin Jiang; Guanghua Yang; Ting Liu; Xiaodong Zhou; Xiaohui Li; Rui Sheng; Lang Liu (Fuel, 2026)

Copper isotope perspective on sulfide-silicate liquid immiscibility - Li-Juan Zhu; Lie-Meng Chen; Peter C. Lightfoot; Sheng-Ao Liu; Dan-Dan Li; Song-Yue Yu; Rui-Zhong Hu (Geochimica et Cosmochimica Acta, 2026)

Enhancing photosynthesis and stress tolerance of the cyanobacterium Nostoc sphaeroides by adaptive laboratory evolution via dry-wet cycles - Zhen Chen; Rui Liu; Yu-Qing Peng; Zhang-Zhuo-Ya Wang; Yong-Qi Yin; Sheng Du; Yu-Jie Jin; Kui Xu; Fei-Fei Li; Wei-Zhi Li; Shan Zhang; Hua-Hua Yue; et al. (Algal Research, 2026)

Characterisation of Xianling Cifang Formula and its metabolites in the mice lung tissue and blood by UHPLC–HR-MS method - Rui Yang; Yixuan Wang; Yeying Jin; Guohui Han; Sheng Liu (Natural Product Research, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Six-component load reconstruction for offshore wind turbine blades considering deformation-induced additional moments - Baoxuan Wang; Xu Liang; Lizhong Wang; Fangyuan Sheng; Xiang Wang; Yue Chen; Jianwei Zhang; Shengjie Rui; Rui Liu (Ocean Engineering, 2026)

Magmatic source effects on Zircon Eu anomalies: Refining the Late Cretaceous–Eocene uplift of the Gangdese Arc, Southern Tibet - Guang-Sheng Ren; Jin-Gen Dai; Xiang-Rui Liu; Xu Han; Bo-Rong Liu; Jia-Qi Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Climate risk: toppling the dominoes of the low-altitude economy industrial chain - Chang Liu; Shiyu Sheng; Zebin Zhao; Rui Cheng (Environment, Development and Sustainability, 2026)

Insights into the effects of different nitrogen sources on microbial metabolic function and biodegradation of bituminous coal - Yundu Yang; Bingjun Liu; Sheng Xue; Junyu Wang; Xiangqing Jiang; Ruifeng Chen; Rui Sun; Keyang Cheng (Fuel, 2026)

Interfacial charge transfer bridge enables high-quality heterojunction for braided coaxial ammonium-ion asymmetric supercapacitors - Jing Xu; Sheng-Jie Wang; Mao-Lan Liao; Zi-Tao Yang; Jia-Peng Hu; Rui-Lai Liu; Jia-Huan Tang; Zhi-Feng Zheng; Yi-Bing Xie (Chemical Engineering Journal, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Photo-driven valorization of lactate in human sweat for controllable production of fuels and value-added chemicals - Yu Gao; Rui Zhu; Tengteng Han; Tianran Sheng; Xiaodong Liu; Ming Zhou; Yuchen Ding; Yude Su (Chemical Engineering Journal, 2025)

High-yield synthesis of biomass-derived carbon dots for enhanced taraxacum growth - Guanxiong Liu; Hui Wang; Jiaxin Dong; Yinying He; Rui Wang; Xiangli Li; Dongyue Liu; Jing Duan; Jing Feng; Xiaoyu Lu; Lijuan Gui; Sheng Hou; et al. (Biomass and Bioenergy, 2025)

Chemical constituents of Tinospora hainanensis and their chemotaxonomic significance - Ming-Hua Wang; Rui Ao; Bao-Qiang Liu; Juan Zhang; Jun-Sheng Zhang (Biochemical Systematics and Ecology, 2025)

Integrated multi-omics analysis of UL16-binding protein 2 as a prognostic and immunotherapy biomarker for colorectal cancer - Xin-Yang Qu; Yong Xu; Rui-Min Wu; Gao-Chun Xiao; Ping-Feng Wang; Jin Xie; Xu-Sheng Liu (Functional & Integrative Genomics, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Discovery of ca. 2.33–2.22 Ga magmatic activities in the Longshan Complex bordering the southwestern margin of the North China Craton: Implications for tectonic transformation - Yi-Yi Zhang; Jun-Sheng Lu; Rui-Ying Zhang; Yu-Ting Li; Xu Kong; Gang Liu; Qiang Feng; Zeng-Yin Duan; Juan-Juan Li (Lithos, 2025)

Constructing MoxTi1-x catalytic pairs to enhance photoelectron transfer for emerging contaminants photocatalytic removal - Hai-Yuan Chi; Jian-bin Su; Sheng-tai Hou; Ze-hua Wang; Xi-tong Li; Wen-long Zhang; Hong-jie Wang; Rui Liu (Journal of Cleaner Production, 2025)

Study on the reaction mechanism of nitrogen-containing gases from polyurethane pyrolysis with carbonate molten salts - Yang-Hai Zheng; Jun-Qiang Rui; Sheng-Rong Guo; Cheng Yao; Zhao-Yang Liu; Yun Xue; Ju-Yue Yang; Yong-De Yan (Fuel, 2025)

Multiscale yttrium-stabilized pillaring and fluorinated interphase engineering enable fast Mn redox toward 5C-level layered sodium oxide - Yuanyuan Liu; Qiwen Ran; Wanyue Sheng; Hanxiao Chang; Rui Cao; Jintao Liu; Mingqi Li; Xingquan Liu; Sridhar Komarneni (Chemical Engineering Journal, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Revealing the occurrence characteristics, interaction mechanisms, and health risk of phthalates in agricultural soil of arid regions across Northwest China - Guo-dong Kang; Peng Lei; Lei-lei Lu; Ning Wang; Meng-jiao Li; Liang-liang Liu; Rui-yun Sun; Sheng-hu Zhang; Yan-hua Liu; Ping Wu (Environmental Monitoring and Assessment, 2025)

Spatiotemporal patterns of fecal cortisol metabolites in critically endangered wild Alpine musk deer in eastern edge regions of Tibetan Plateau: influencing factors and conservation implications - Jiayi Wu; Xiaoping Lu; Shuo Geng; Liquan Shen; Gong Wang; Rui Liu; Jun Qi; Chunting Feng; Junyi Yang; Zhengxu An; Rongxin Li; Na Qiao; et al. (Biologia, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Dithiothreitol oxidative potential (OP) of PM2.5 in Beijing: Quantitative contribution of metals to OP and its prediction based on machine learning models - Yusheng Ma; Mengshuang Sheng; Jing Shang; Rui Tang; Jiong Cao; Yuhan Liu; Chenyu Liang; Yu Kuang; Yan Zheng; Zhen Cheng; Rico K.Y. Cheung; Robin L. Modini; et al. (Journal of Hazardous Materials, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Au-modified Cu2O with CO-enriched active sites for tandem catalysis of CO2 deep-reduction to C2H4 - Ji-song Yan; Wei Qiu; Hao Liu; Qing-shan Wang; Ling-qi Yu; Sheng-hui Guo; Rui-tang Guo (Journal of Environmental Chemical Engineering, 2025)

Hydrophobically modified Cu-ZnO-Al2O3 catalyst for CO2 hydrogenation to methanol - Xiuyun Jiang; Jucang Ke; Rui Li; Hao Huang; Zhihao Liu; Haozhe Feng; Qingxiang Ma; Xinhua Gao; Guangbo Liu; Xiaobo Feng; Tian-Sheng Zhao; Noritatsu Tsubaki (Journal of Environmental Chemical Engineering, 2025)

Isotope tracer study of soil erosion in a typical sub-watershed in the eastern Tianshan Mountains, China - Ninglu Zhang; Jianjun Yang; Wenli Xing; Xinyu Liu; Feifei Sheng; Wanqing Zhao; Zhiguang Zhang; Ziqi Tian; Rui Chen (Journal of Environmental Radioactivity, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

A new benzophenone derivative from Aspergillus fumigatus WJ-131 - Jia-Qi Liu; Sheng-Qi Zhang; Xiu-Hong Wu; Shuai-Xing Liu; Rui-Dang Yang; Liang Deng; Le Cai (Natural Product Research, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Recent progress of piezoelectric materials applied in photocatalytic CO2 reduction: A review - Yi-fu Liu; Rui-tang Guo; Sheng-hui Guo; Ling-qi Yu; Ji-song Yan; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Preferred crystal surface exposure and near-crystal surface desolvation construct efficient Zn plating/stripping reversibility - Zihan Qi; Murong Xi; Zhenjie Liu; Rui Sheng; Wei Wang; Tianlong Wu; Yudai Huang (Chemical Engineering Journal, 2024)

Relative importance of altitude shifts with plant and microbial diversity to soil multifunctionality in grasslands of north-western China - Ning Wang; Junhui Cheng; Yunhua Liu; Qicheng Xu; Chen Zhu; Ning Ling; Junjie Guo; Rui Li; Wei Huang; Shiwei Guo; Baorong Wang; Shaoshan An; et al. (Plant and Soil, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

The role of male hormones in bacterial infections: enhancing Staphylococcus aureus virulence through testosterone-induced Agr activation - Zhaoxia Luo; Huimin Xi; Wei Huang; Mei-fang Liu; Lei Yuan; Qiang Chen; Yanghua Xiao; Qing Zhu; Rui Zhao; Yi-yun Sheng (Archives of Microbiology, 2024)

Megastigmane glycosides from the traditional Uighur medicine Cydonia oblonga Mill. - Shan-Shan Jiao; Rui-Feng Ding; Xin Yuan; Xiao-Ping He; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2024)

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.

Assessing the ecological security of the Three Gorges reservoir complex ecosystem based on the improved three-dimensional emergy ecological footprint model - Peiran Jing; Jinbao Sheng; Yi Wang; Tiesong Hu; Lidan Guo; Rui Zhu; Kai Dong; Ali Mahmoud; Yong Liu; Xiang Li (Science of The Total Environment, 2024)

Diclofenac sodium effectively inhibits the biofilm formation of Staphylococcus epidermidis - Huimin Xi; Zhaoxia Luo; Mei-fang Liu; Qiang Chen; Qing Zhu; Lei yuan; Yi-yun Sheng; Rui Zhao (Archives of Microbiology, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

A biotechnological approach for suspended solids removal in biogas slurry via microbially induced calcite precipitation (MICP) - Rui Wang; Chao-Sheng Tang; Xiaohua Pan; Zhengtao Shen; Yujia Liu; Xiancai Lu (Journal of Cleaner Production, 2024)

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

Synergistic effects of chemical additives and mature compost on reducing H2S emission during kitchen waste composting - Yongdi Liu; Haihou Wang; Hao Zhang; Yueyue Tao; Rui Chen; Sheng Hang; Xiaoyan Ding; Meidi Cheng; Guochun Ding; Yuquan Wei; Ting Xu; Ji Li (Journal of Environmental Sciences, 2024)

Snakehead vesiculovirus (SHVV) leader RNA interacts with host antiviral factors RPS8 and L13a and promotes virus replication - Yan Ji; Rui Cheng; Xuan Zhou; Jiaqi Zhang; Xiaodan Liu; Suhong Sheng; Chi Zhang (Fish & Shellfish Immunology, 2024)

Experimental investigation of propeller blade back cavitation induced pressure pulses by synchronous observation - Rui Wu; Heng Liu; Weiqi Chen; Sheng Ji; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Ultrafine FeCuAgCeGd–based high–entropy nanozyme: Preparation, catalytic mechanism, and point–of–care detection of dopamine in human serum - Rui Sheng; Yue Liu; Taimei Cai; Rong Wang; Gan Yang; Tao Wen; Fangjian Ning; Hailong Peng (Chemical Engineering Journal, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

De-branching of starch molecules enhanced the complexation with chitosan and its potential utilization for delivering hydrophobic compounds - Min Liu; Min Zhuang; Dengdeng Li; Jinxu Fan; Rui Wang; Xuanyu Wang; Sheng Ke; Ming Ning; Zhongkai Zhou (Food Hydrocolloids, 2024)

Experimental and theoretical study on seismic behavior of a new UHPFRC sandwich wall and wall-wall joint - Ru-Rui Liu; Ran Ding; Yong-Tao Sun; Jian-Sheng Fan; Ding-Qiu Chen; Jian-Chao Xu (Engineering Structures, 2024)

Numerical study on uplift capacity and behavior of plate anchor considering different dilation angles - Yong-sheng Wang; Wei Ye; Hao Liu; Quanping Gao; Ji-xin Li; Rui-heng Ding; Rui Rui (Arabian Journal of Geosciences, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Nickel isotope fractionation during intense weathering of basalt: Implications for Ni output from continental weathering - Sheng-Sheng Sun; Teng-Hao-Bo Deng; Ming Ao; Wen-Jun Yang; Xiao-Rui Liu; Ting Liu; Jian-Ming Zhu; Jean Louis Morel; Ye-Tao Tang; Rong-Liang Qiu (Geochimica et Cosmochimica Acta, 2024)

Boosting ion diffusion kinetics of Fe2O3/MoC@NG via heterointerface engineering and pseudocapacitance behavior: An alternative high-rate anode for high‐capacity lithium dual-ion batteries - Juan Ding; Yudai Huang; Wenhua Cheng; Rui Sheng; Zhenjie Liu; Xingchao Wang; Yong Guo; Jiulin Wang; Dianzeng Jia; Xincun Tang; Lei Wang (Chemical Engineering Journal, 2024)

Growth characteristics and biomass model of Cupressus gigantea sapling - Liu Chang-Sheng; Li Tao; Zhang Rui-wen; Wang Chao; Qu Xing-le; Luo Da-qing (Trees, 2024)

Investigating the Immunogenic Cell Death-Dependent Subtypes and Prognostic Signature of Triple-Negative Breast Cancer - Youyang Shi; Yuanyuan Wu; Feifei Li; Kexin Jiang; Xiaofang Fang; Yu Wang; Xiaoyun Song; Rui Wang; Lixin Chen; Jinzhou Zheng; Chunyu Wu; Yuenong Qin; et al. (Phenomics, 2024)

CaO hydrated with ethanol solution for flue gas HCl immobilization. Part II: Influences of gas components - Rui Wang; Xiaoshuo Liu; Cong Chen; Yuqing Wang; Zhen Shen; Lei Meng; Xiaobing Gu; Changdong Sheng; Yufeng Duan (Fuel, 2023)

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Subchronic exposure to di-(2-ethylhexyl) phthalate (DEHP) elicits blood–brain barrier dysfunction and neuroinflammation in male C57BL/6J mice - Wen-qiang Ren; Nuo Liu; Yan Shen; Xian-yan Wang; Qiong Zhou; Chen Rui; Xiao-han Yang; Sheng-long Cao; Ling-yu Li; Yán Wāng; Qu-nan Wang (Toxicology, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

CaO hydrated with ethanol solution for flue gas HCl immobilization. Part Ⅰ: Modification & dechlorination - Rui Wang; Xiaoshuo Liu; Cong Chen; Yuqing Wang; Zhen Shen; Lei Meng; Xiaobing Gu; Changdong Sheng; Yufeng Duan (Fuel, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

CRISPR-Cas12a powered multifunctional DNA nanodumbbell lock biosensor for multiple molecular detection - Yuqing Zhu; Xiaohe Zheng; Rui Zhu; Hongrui Zhao; Hongli Zhai; Feiyang Qian; Tenghua Zhang; Zihui Xie; Silan Liu; Bowen Jiang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

Subassembly Partition of Hull Block Based on Two-Dimensional PSO Algorithm - Bo Liu; Rui Li; Ji Wang; Yujun Liu; Sheng Li (Journal of Marine Science and Engineering, 2023)
Subassembly partition is an important process in hull block building as it greatly affects the efficiency and quality of the assembly work. Recently, an experience-based method has been widely applied to the subassembly partition process, which consumes much design time and manpower, thus causing more challenges toward a more highly automated and efficient stage in this process. To shorten the gap, an automated subassembly partition method is presented in this study. First, the assembly information model is defined with essential attributes and topological relations of the parts. Second, an optimization model is established with consideration of a trade-off between the intra-cluster cohesion and cluster number on the premise of satisfying certain constraints. After that, considering the fuzziness and diversity of the subassembly partition problem, a two-dimensional coding discrete particle swarm optimization (PSO) algorithm is developed. Finally, two blocks are demonstrated as instances to verify the proposed method, and the results show that the proposed method is feasible and applicable to the block with a flat structure.

Increased hypertension risk for the elderly with high blood levels of strontium and lead - Jiebao Zhang; Chunfang Xu; Yan Guo; Xingyi Jin; Zi Cheng; Qi Tao; Lin Liu; Rui Zhan; Xuemin Yu; Hongjuan Cao; Fangbiao Tao; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Abundance and characteristics of microplastics in the Wanquan River estuary, Hainan Island - Tuan-Tuan Wang; Wang-Qing Tang; Dong-Hai Wu; Xin-Rui Yu; Guang-Yu Wang; Xing-Wei Cai; Shuai Shao; Sai Wang; Ling Mo; You-Sheng Liu; Guang-Guo Ying; Zhong-Bing Chen (Marine Pollution Bulletin, 2023)

A novel solvent system of polyamides achieves new application in ZIBs by aggregation induced Lewis acid-base centers - Murong Xi; Zhenjie Liu; Rui Sheng; Jiafeng Zhu; Yong Guo; Juan Ding; Xingchao Wang; Yue Zhang; Lei Wang; Zhipeng Sun; Wenjun Zhang; Jiulin Wang; et al. (Chemical Engineering Journal, 2023)

Territorial function differentiation and its comprehensive regionalization in China - Jie Fan; Kan Zhou; Kerong Sheng; Rui Guo; Dong Chen; Yafei Wang; Hanchu Liu; Zheng Wang; Yong Sun; Jie Zhang; Jianxiong Wu; Hao Zhao (Science China Earth Sciences, 2023)

Branch development in monoculture and mixed-species plantations of Betula alnoides, Erythrophleum fordii and Pinus kesiya var. langbianensis in southwestern China - Kai-Li Liu; Chun-Sheng Wang; Bo-Yao Chen; Rui-Hui Wang; Jie Zeng (Forest Ecology and Management, 2023)

Effects of combined application of nitrogen, phosphorus, and potassium fertilizers on tea (Camellia sinensis) growth and fungal community - Sheng Tang; Jingjie Zhou; Wankun Pan; Tao Sun; Mengjiao Liu; Rui Tang; Zijing Li; Qingxu Ma; Lianghuan Wu (Applied Soil Ecology, 2023)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Correction to: Desiccation cracking in clay‑bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao‑Sheng Tang; Hao Xu; Xiang‑Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

Desiccation cracking in clay-bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao-Sheng Tang; Hao Xu; Xiang-Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

Impacts of anthropogenic disturbances on microbial community of coastal waters in Shenzhen, South China - Rui Zhang; Wen-chao Liu; Yu Liu; Hong-lian Zhang; Zhi-hui Zhao; Ling-yun Zou; Yu-chun Shen; Wen-Sheng Lan (Ecotoxicology, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Puerhibacterium puerhi gen. nov., sp. nov., a novel member of the family Promicromonosporaceae, isolated from Pu-erh tea pile-fermentation - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Lu Han; Wen-Shu Peng; Li Liu; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Association Between Blood Heavy Metal Concentrations and Dyslipidemia in the Elderly - Xingmeng Zhu; Yong Fan; Jie Sheng; Ling Gu; Qi Tao; Rui Huang; Kaiyong Liu; Linsheng Yang; Guimei Chen; Hongjuan Cao; Kaichun Li; Fangbiao Tao; et al. (Biological Trace Element Research, 2021)

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

The role of miRNA-155 in monocrotaline-induced pulmonary arterial hypertension through c-Fos/NLRP3/caspase-1 - Shou-Dong Chai; Zhen-Kun Li; Rui Liu; Tao Liu; Ming-Feng Dong; Pei-Zhe Tang; Jian-Tang Wang; Sheng-Jun Ma (Molecular & Cellular Toxicology, 2020)

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Characteristics and dynamics of the Ganqiuchi rock avalanche triggered by a paleo-earthquake in the Northern Qinling Mountains - Ze-Hua Zhou; Yan Lyu; Sheng-rui Su; Shi-jie Liu; Hui Zhao; Peng Li; Yang Zhou (Journal of Mountain Science, 2020)

ABA signaling rather than ABA metabolism is involved in trehalose-induced drought tolerance in tomato plants - Wenqing Yu; Ruirui Zhao; Liu Wang; Shujuan Zhang; Rui Li; Jiping Sheng; Lin Shen (Planta, 2019)

The effects of codon usage on the formation of secondary structures of nucleocapsid protein of peste des petits ruminants virus - Xiao-xia Ma; Yi-ning Wang; Xiao-an Cao; Xue-rui Li; Yong-sheng Liu; Jian-hua Zhou; Xue-peng Cai (Genes & Genomics, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Enhanced drought tolerance in tomato plants by overexpression of SlMAPK1 - Liu Wang; Ruirui Zhao; Rui Li; Wenqing Yu; Meijing Yang; Jiping Sheng; Lin Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Photoperiodism dynamics during the domestication and improvement of soybean - Sheng-Rui Zhang; Huan Wang; Zhongyu Wang; Yao Ren; Lifang Niu; Jun Liu; Bin Liu (Science China Life Sciences, 2017)

Enhanced dissipation of DEHP in soil and simultaneously reduced bioaccumulation of DEHP in vegetable using bioaugmentation with exogenous bacteria - Hai-Ming Zhao; Rui-Wen Hu; He-Biao Huang; Hong-Fei Wen; Huan Du; Yan-Wen Li; Hui Li; Quan-Ying Cai; Ce-Hui Mo; Jie-Sheng Liu; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

Characterization of angiotensin-І converting enzyme inhibiting peptide from Venerupis philippinarum with nano-liquid chromatography in combination with orbitrap mass spectrum detection and molecular docking - Lei Shi; Tizhi Wu; Naijuan Sheng; Li Yang; Qian Wang; Rui Liu; Hao Wu (Journal of Ocean University of China, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Investigating the Effect of Tissue Size on Mycelial Growth of Seven Mushroom Species by Using a Novel Device for Precise Tissue Isolation - Sheng-Rong Liu; Wei-Rui Zhang; Ai-Ping Chen; Yun-Bo Kuang (Indian Journal of Microbiology, 2016)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

Quantitative determination constraints on dolomitization model for the Upper Permian Changxing reservoir dolomites of Northeastern Sichuan Basin, Southwestern China - Rui Zhao; Ya Sheng Wu; Hong Xia Jiang; Qing Song Liu; Li Jing Liu (Carbonates and Evaporites, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Integrated SWAT model and statistical downscaling for estimating streamflow response to climate change in the Lake Dianchi watershed, China - Jing Zhou; Dan He; Yufeng Xie; Yong Liu; Yonghui Yang; Hu Sheng; Huaicheng Guo; Lei Zhao; Rui Zou (Stochastic Environmental Research and Risk Assessment, 2015)

Screening of Inherited Metabolic Disorders in Infants with Infantile Spasms - Xiao-Ming Liu; Rui Li; Sheng-Zhi Chen; Yan Sang; Jiao Chen; Cong-Hai Fan (Cell Biochemistry and Biophysics, 2015)

Ground-dwelling arthropod community response to native grassland conversion in a temperate desert of northwestern China - Qi Feng; Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Li-Juan Chen (Journal of Insect Conservation, 2015)

Snail regulated by PKC/GSK-3β pathway is crucial for EGF-induced epithelial-mesenchymal transition (EMT) of cancer cells - Zong-cai Liu; Xiao-hui Chen; Hai-xing Song; Hong-sheng Wang; Ge Zhang; Hao Wang; Dan-yang Chen; Rui Fang; Hao Liu; Shao-hui Cai; Jun Du (Cell and Tissue Research, 2014)

Transcription of the Human Sodium Channel SCN1A Gene Is Repressed by a Scaffolding Protein RACK1 - Zhao-Fei Dong; Ling-Jia Tang; Guang-Fei Deng; Tao Zeng; Shu-Jing Liu; Rui-Ping Wan; Ting Liu; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

A novel variant in the 3′ UTR of human SCN1A gene from a patient with Dravet syndrome decreases mRNA stability mediated by GAPDH’s binding - Tao Zeng; Zhao-Fei Dong; Shu-Jing Liu; Rui-Ping Wan; Ling-Jia Tang; Ting Liu; Qi-Hua Zhao; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Human Genetics, 2014)

Origin of the Miocene porphyries and their mafic microgranular enclaves from Dabu porphyry Cu–Mo deposit, southern Tibet: implications for magma mixing/mingling and mineralization - Song Wu; You-Ye Zheng; Xiang Sun; Sheng-Ao Liu; Rui-Rui Geng; Zhi-Ming You; Hai-Tao Ouyang; Dong Lei; Zhong-Ying Zhao (International Geology Review, 2014)

Genome-Wide Identification, Classification, Expression Profiling, and SSR Marker Development of the MADS-Box Gene Family in Citrus - Xiao-Jin Hou; Sheng-Rui Liu; Muhammad Rehman Gul Khan; Chun-Gen Hu; Jin-Zhi Zhang (Plant Molecular Biology Reporter, 2014)

Converting natural vegetation to farmland alters functional structure of ground-dwelling beetles and spiders in a desert oasis - Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Bo-Wen Jin; Li-Juan Chen (Journal of Insect Conservation, 2014)

High-performance liquid chromatography with fluorescence detection for the determination of nitrofuran metabolites in pork muscle - Liang-Quan Sheng; Ming-Ming Chen; Shui-Sheng Chen; Na-Na Du; Zhao-Di Liu; Chong-Fu Song; Rui Qiao (Food Additives & Contaminants: Part A, 2013)

Correlation of Nr4a2 Expression with the Neuron Progenitors in Adult Zebrafish Brain - Sheng Chen; Guang Rui Luo; Ting Li; Ting Xi Liu; Weidong Le (Journal of Molecular Neuroscience, 2013)

Effects of the Conversion of Native Vegetation to Farmlands on Soil Microarthropod Biodiversity and Ecosystem Functioning in a Desert Oasis - Feng-Rui Li; Qi Feng; Ji-Liang Liu; Te-Sheng Sun; Wei Ren; Zhen-Huan Guan (Ecosystems, 2013)

The effects of three years of fencing enclosure on soil seed banks and the relationship with above-ground vegetation of degraded alpine grasslands of the Tibetan plateau - Zhan-Huan Shang; Bin Deng; Lu-Ming Ding; Guo-Hua Ren; Guo-Sheng Xin; Zhi-Yun Liu; Yan-Long Wang; Rui-Jun Long (Plant and Soil, 2013)

Effects of low nitrogen and drought stresses on proline synthesis of Jatropha curcas seedling - Wen-Guo Wang; Rui Li; Bin Liu; Liang Li; Sheng-Hua Wang; Fang Chen (Acta Physiologiae Plantarum, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Isolation and Analysis of Rice Rf1-Orthologus PPR Genes Co-segregating with Rf3 in Maize - Xiang-Bo Xu; Zhan-Xian Liu; Deng-Feng Zhang; Ying Liu; Wei-Bin Song; Jian-Sheng Li; Jing-Rui Dai (Plant Molecular Biology Reporter, 2009)

PEG-conjugated PAMAM Dendrimers Mediate Efficient Intramuscular Gene Expression - Rong Qi; Yu Gao; Yin Tang; Rui-Rui He; Tao-Le Liu; Yun He; Sheng Sun; Bo-Yu Li; Yang-Bing Li; George Liu (The AAPS Journal, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

The wheat TaGI1, involved in photoperiodic flowering, encodesan Arabidopsis GI ortholog - Xiang Yu Zhao; Mao Sen Liu; Jia Rui Li; Chun Mei Guan; Xian Sheng Zhang (Plant Molecular Biology, 2005)